2022
DOI: 10.17850/njg102-4-2
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphy and palaeosol profiles of the Upper Triassic Isfjorden Member, Svalbard

Abstract: The Isfjorden Member forms the upper part of the De Geerdalen Formation in Svalbard and is well exposed throughout central and eastern Spitsbergen, including the island of Wilhelmøya. We examine palaeosol profiles identified in the Isfjorden Member and compare these to profiles seen in the remainder of the De Geerdalen Formation. In addition, we address the nuances of the Isfjorden Member, its practicality as a stratigraphic interval and attempt to constrain the unit's presence, as well as the nature of its lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 0 publications
0
10
1
Order By: Relevance
“…The Hopen Member, defined by Lord et al (2014a), is not present at any of the localities visited in this study -nor are the characteristic facies of the Isfjorden Member present on the island of Hopen.…”
Section: Upper Triassic Stratigraphymentioning
confidence: 70%
See 2 more Smart Citations
“…The Hopen Member, defined by Lord et al (2014a), is not present at any of the localities visited in this study -nor are the characteristic facies of the Isfjorden Member present on the island of Hopen.…”
Section: Upper Triassic Stratigraphymentioning
confidence: 70%
“…The stratigraphy and sedimentology of the Upper Triassic succession in Svalbard can largely be considered as well studied. Early works by Buchan et al (1965), Worsley (1973), Smith (1975), Smith et al (1975), Lock et al (1978), Pčelina (1980Pčelina ( , 1983 and Mørk et al (1982Mørk et al ( , 1999Mørk et al ( , 2013 conducted primary mapping studies and identified the first Triassic stratigraphic units, whilst Mørk et al (1982), Anell et al (2014Anell et al ( , 2016Anell et al ( , 2020, Klausen & Mørk (2014), Klausen et al (2015Klausen et al ( , 2016Klausen et al ( , 2019, Rød et al (2014), Lord et al (2014aLord et al ( , b, 2017 focused on the nuances of facies studies and correlation of Upper Triassic sequences throughout Svalbard and the Barents Sea. The Longyearbyen CO 2 Lab Dh4 well and the diagenetic properties of a proposed Upper Triassic to Lower Jurassic reservoir interval were investigated by Mørk (2013).…”
Section: Upper Triassic Stratigraphymentioning
confidence: 99%
See 1 more Smart Citation
“…The well-preserved fluvial channel fill sandstone bodies are prominently exposed in the steep cliff sides of the island. Whilst these are relatively isolated in their stratigraphic position and encased in a highly heterolithic succession they clearly indicate the presence of relatively good reservoir quality rocks in the region (Lord et al, 2014(Lord et al, : 2017.…”
Section: Triassic To Middle Jurassic (Tse 5)mentioning
confidence: 95%
“…Local highs throughout the eastern part of the SCTSE existed with the Induan part of the succession missing in many places (Mørk et al, 1999;Lord et al, 2017;Vigran et al, 2014).The prodeltaic part of this delta system is represented by the Tschermakfjellet Formation (Ladinian/early Carnian), whereas the overlying De Geerdalen Formation (Carnian to early Norian) represent delta slope to delta front and delta plain depositional environment (Fig. 4) (Klausen and Mørk 2013;Lord et al, 2014;2017;Rød et al, 2014). On Edgeøya, fluvial, tidal and delta front deposits are documented in the De Geerdalen Formation, with thick sandstone intervals featuring a lobate geometry found in many parts of the strata (Rød et al, 2014).…”
Section: Lithostratigraphy and Depositional Systemsmentioning
confidence: 99%